2013
DOI: 10.1080/03079457.2013.776161
|View full text |Cite
|
Sign up to set email alerts
|

The role of an attenuated anticoccidial vaccine on the intestinal ecosystem and on the pathogenesis of experimental necrotic enteritis in broiler chickens

Abstract: The objective of the present study was to investigate the effect of an attenuated anticoccidial vaccination on the intestinal ecosystem and on the pathogenesis of experimental necrotic enteritis (NE) in broiler chickens. Two hundred and forty 1-day-old Cobb 500 broiler chickens were randomly allocated to four treatment groups according to the following experimental design: control Group N; Group PN, where birds were vaccinated with anticoccidial vaccine; Group M, where birds were challenged with Clostridium pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 29 publications
2
35
0
7
Order By: Relevance
“…Thus, vaccination prevented not only coccidia-specific lesions what is known from previous investigations (e.g., Shirley et al, 1995;Williams, 2003;Awad et al, 2013) but also NE lesions. This is consistent with the findings of Tsiouris et al (2013) who recently described the positive effect of anticoccidial vaccination on intestinal NE lesions as well as on C. perfringens counts in their complex subclinical NE model.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, vaccination prevented not only coccidia-specific lesions what is known from previous investigations (e.g., Shirley et al, 1995;Williams, 2003;Awad et al, 2013) but also NE lesions. This is consistent with the findings of Tsiouris et al (2013) who recently described the positive effect of anticoccidial vaccination on intestinal NE lesions as well as on C. perfringens counts in their complex subclinical NE model.…”
Section: Discussionsupporting
confidence: 94%
“…vaccine in prevention of clinical NE caused by mixed infections with E. tenella, E. brunetti and NetB positive C. perfringens. Up to now, most studies dealing with anticoccidial vaccines and NE aimed at induction of the disease employing vaccines (generally at overdoses) as predisposing factors to clostridial infections (Williams, 2003;McReynolds et al, 2004;Gholamiandehkordi et al, 2007) except of one study in a subclinical model describing the effect of vaccination against coccidiosis to prevent NE (Tsiouris et al, 2013). The trials described herein are based on a clinical model since most of the unvaccinated coinfected animals showed moderate to severe signs of clinical disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The gizzards were scored for gross lesions by the use of a 0 to 2 scale, described by Novoa-Garrido et al (2006). The livers were scored using a 0 to 2 scale, described by Tsiouris et al (2013), giving a score 0 when no gross lesions were observed, a score 1 when liver congestion and/or gall bladder distension and wall thickening and/or bile discoloration were observed, and a score 2 when necrotic lesions in liver were observed.…”
Section: Methodsmentioning
confidence: 99%
“…Although, netB-positive Clostridium perfringens type A strain is the causal agent of the disease, a number of cofactors are usually required to precipitate an outbreak of the disease, such as damage to the intestinal mucosa and increase of pH and viscosity of intestinal digesta (Kaldhusdal et al, 1999;McReynolds et al, 2007;Tsiouris et al, 2013). Various preventive and curative measures have been proposed to control necrotic enteritis Timbermont et al, 2010), including changes in feeding management (Mateos et al, 2002).…”
Section: Introductionmentioning
confidence: 99%